Perlindungan Hukum Terhadap Konsumen Pre Project Selling Perusahaan Pengembang Properti Yang Dinyatakan Pailit: Legal Protection Of Pre-Project Selling Consumers Of Property Development Company Declared Bankrupt - Muniefiy, Nawal Zidan El; Santoso, Budi; Ganindha, Ranitya (WARKAT, 2023)
Pre-Project Selling consumers are in the weakest position in bankruptcy, because in addition to being the last creditor, consumers also cannot be said to be the owner if there is no AJB. The Curator's action to put the apartment building into bankruptcy is in accordance with the provisions of the law. Legal protection involves both preventing and repressive protections. In terms of preventive action, the sale and purchase agreement (PPJB) legally made according to Article 1338 of Civil Law serves as the law governing all parties in the contract. The PPJB which is binding to both consumers and business people sets forth rights and obligations that both have to understand. The rights of the consumers involve receiving the house as the object within the time as agreed upon. Moreover, the law requires the business people to run the business in good faith. The parties responsible to provide goods and/or services according to the orders made must not break the terms set out in a contract and must provide redress. This redress consists of that given through commercial court, consumer redress according to the position as concurrent creditors, or redress of the company through civil lawsuits. Law concerning bankruptcy and Consumer Protection Law have different solutions, but these two laws affect each other and are connected when a property company is declared bankrupt.